High level employees perceptions of the research and evaluation division and its work: a qualitative study - Schaefer, Kal (BRAC Research and Evaluation Division (RED), 2019)
The purpose of this study is to examine the role of BRAC's Research and Evaluation Division and how it provides information and support to BRAC's high level employees in program development, planning and management. Data was collected from 15 employees through interviews and focused discussions with two people outside the target group during January 2000. After a short introduction and some remarks on the methodology used in this study, the main chapter, that deals with the participants critiques, complaints and suggestions follows. The findings of this study clearly showed that the participants are quite satisfied with the improvement of RED in the last couple years. However, the results also reveal the need for further improvement. These include very specialized suggestions, such as the methodology used in the studies, to highly general complaints about a lack of interaction and communication. The study paper closes with some conclusions and personal remarks.